Reflections on Disability: Perspectives on South Africa, India and the United States of America - Buga, Harriette (Institute of Development and Labour Law, 2014)
The aim of this paper is to reflect on disability and social protection in three jurisdictions. [...] Section 1 provides an overview of the concept of disability. The background and trend disability has taken from the post-war period, which provided quota systems for the war veterans who were disabled by war to the alternative approach of anti-discrimination. The section will also discuss disability as a human rights issue and will give an overview of international organizations implementing the rights of disabled persons. Section 2 will deal with the definition and prevalence of disability in South Africa. It also discusses the fragmented nature of disability and the legal frame work to support and protect disabled persons, and the challenges and problems faced in implementing policies to protect disabled people. This Section will also look at legislation that has been enacted to include people with disabilities. Section 3 will deal the definition and prevalence of disability in India. In India has approximately 5 to 6 percent of its total population is disabled. This Section will discuss the legal framework that has been enacted to support and protect disabled persons. It will also deal with the challenges faced in the implementation and monitoring of disability policies in India. Section 4 will deal with disability in the United States. The United States has very strong advocates for disability rights. This chapter will deal with the legal framework that has been enacted to protect the disabled persons. It will also look at the disability benefit systems and the challenges they face. Finally the section will discuss the conflict that exists between the Americans with Disabilities Act (ADA) and the Social Security Disability Insurance (SSDI) Sections 5 and 6 will deal with the conclusion recommendations respectively.